A correspondence between IBA-1 and IBA-2 Models of even isotopes of Sm - Sharrad, Fadhil; Okhunov, Abdurahim (National Academy of Sciences of Armenia, 2012)
The level scheme of the 148,150,152,154,156,158Sm isotopes have been investigated using both IBA-1 and IBA-2 versions of Interacting Boson Approximation Model. IBA-1 and IBA-2 Hamiltonian parameters are obtained as well as the extraction of the energy levels. Also, the electric quadrupole transition probabilities ( 2 : ) i f B E J → J of the Sm isotopes were calculated. In calculations, the theoretical energy levels and the electric quadrupole transition probabilities have been obtained by using PHINT code. Good agreement was found from comparison between the calculated energy levels and the electric quadrupole transition probabilities B(E2) of the Sm isotopes with the experimental data.